Effects of roof geometric details on aerodynamic performance of standing seam metal roofs. (15th December 2020) - Azzi, Ziad; Habte, Filmon; Vutukuru, Krishna Sai; Gan Chowdhury, Arindam; Moravej, Mohammadtaghi
Highlights: Performance of standing seam metal roofs in large-scale testing. Partial turbulence simulation method to correct for missing low-frequency spectrum. Comparison on a tap by tap and area averaged bases. Standing seam metal roofs exhibited less peak negative pressures and fluctuations. Roof configuration reduced the power spectral densities of pressure fluctuations. Roof configuration lowered the correlation between adjacent taps in corner regions. This study provides realistic dynamic data to Standing Seam Metal Roofing industry. Abstract: Standing seam metal roofs are one of the most commonly used types of roofs especially because of their additional durability and ease of construction. The performance of such roofs under extreme wind events like hurricanes depends on their structural strength and aerodynamic characteristics. Large-scale experimental testing was performed at the NHERI Wall of Wind Experimental Facility (WOW EF) using a 1:10 scale model of a gable-roof building with double-lok trapezoidal seam roof panels along with eave and rake (gable) attachments. The results showed that the geometric features considerably modify the aerodynamic roof pressures. The standing seams along with both types of attachments reduced the peak suction at roof corners as compared to a bare surface roof by as much as 70% and 45% on an individual tap and area-average basis, respectively. In addition, mean uplift pressure reduction was observed. The power spectral densities of pressure fluctuations at most individual taps were also reduced with the addition of attachments. Also, the correlation between the pressures at different taps was significantly decreased in most cases, resulting in reduced area-averaged pressures due to the effects of the standing seams. However, as shown in a previous full-scale study, wind-induced vibrations can lead to damage of such roofs and thus dynamic effects should be carefully considered for design purposes.